2016
DOI: 10.4992/jjpsy.87.15020
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between regulation strategies, emotional and behavioral engagement, and academic achievement

Abstract: 名古屋大学Relationships between regulation strategies, emotional and behavioral engagement, and academic achievement This study examined relationships among regulation strategies, emotional and behavioral engagement, and academic achievement. Regulation strategies included metacognitive and motivational regulation strategies. Motivational regulation strategies have three subtypes: autonomous regulation strategies, cooperative strategies, and performance strategies. A self-reported survey was administered to 199 und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 20 publications
3
10
1
Order By: Relevance
“…This result was inconsistent with that of previous research showing a different underlying mechanism among these three variables, indicating a link from emotion to behavior, which then affected academic performance (Umemoto, Ito, & Tanaka, 2016). Previous research found that behavioral engagement directly influenced academic performance, while emotional engagement was indirectly related to academic performance through behavior, especially among general students at a four-year college than dental students at a six-year college in Japan.…”
Section: The Mechanism Underlying Academic Performancecontrasting
confidence: 91%
“…This result was inconsistent with that of previous research showing a different underlying mechanism among these three variables, indicating a link from emotion to behavior, which then affected academic performance (Umemoto, Ito, & Tanaka, 2016). Previous research found that behavioral engagement directly influenced academic performance, while emotional engagement was indirectly related to academic performance through behavior, especially among general students at a four-year college than dental students at a six-year college in Japan.…”
Section: The Mechanism Underlying Academic Performancecontrasting
confidence: 91%
“…In addition to the effects shown thus far, metacognitive strategies have also been shown to enhance general learning behaviors [13][14][15]. As metacognitive strategies involve individuals' learning processes, they foster general learning behaviors, such as effort, persistence, and behavioral engagement [13,14].…”
Section: The Motivational Function Of Metacognitive Strategies: Promomentioning
confidence: 97%
“…First, metacognitive strategies enhanced behavioral engagement and persistence, mediated by self-efficacy. Past research has long shown the relationships between metacognitive strategies and general learning behaviors [13][14][15][16]. However, the mechanism through which the strategy use promotes general learning behaviors was not sufficiently understood.…”
Section: Mediating Effects Of Self-efficacy Between Metacognitive Strmentioning
confidence: 99%
“…If students have an adequate metacognitive skillset, they should be more likely to direct their learning and engagement in math. Some studies have supported this link, as metacognitive skills have been positively associated with performance in an undergraduate psychology course through behavioral engagement (Umemoto, Ito, & Tanaka, 2016). Whether this pattern exists in math for adolescent students (i.e., students whose metacognitive skills are still developing, Veenman, Van Hout-Wolters, & Afflerbach, 2006) remains an unanswered question.…”
Section: Math Metacognitive Skillsmentioning
confidence: 99%